Microsoft Azure storage : the definitive guide - Valiramani, Avinash (IT best practices series., 2024)
For cloud environments to operate and scale as they should, their storage components must be designed and configured well. Now, there's a complete, best-practice guide to designing, deploying, and managing Azure storage services for maximum performance, scalability, and value. Writing for every professional involved in delivering Azure workloads and services, leading enterprise cloud consultant Avinash Valiramani shows how to make the most of Azure storage tools and services to reduce downtime, avoid unnecessary cost, simplify management, and maintain excellent performance no matter how large you scale. Valiramani addresses a wide spectrum of Azure storage-related tools and offerings, offering practical guidance for all stages of your Azure journey, and all environments, no matter how sophisticated. He presents up-to-date overviews and hands-on drill-downs into Azure blob, file, queue, and table storage; managed disks, Data Share, Data Box, and more. Drawing on extensive experience in widely diverse environments, he combines deep knowledge and practical field advice---systematically helping you make the most of all your Azure investments.